Pengaruh Kunjungan Wisata, UMKM, Restoran dan Hotel terhadap PAD Kota Surabaya Tahun 1989-2018 - Oktasa, Andina; Santoso, Ismanto Hadi; Widyawati, Retno Febriyastuti (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2020)
This study aims to Visits of tour on revenue (PAD) in Surabaya City, analyze the effect of Micro Small Medium Enterprises to revenue (PAD) in Surabaya City, analiyze Restaurant on revenue in Surabaya City, analiyze Hotel on revenue in Surabaya City. This analyze used quantitative approach. The population in this study were tourist visits, Micro Small Medium Enterprises , hotels, restaurants and local original income (PAD) in the city of Surabaya. The sample for this study has a period of 30 years in 1989-2018. The analytical method used in this study uses multiple linear regression analysis techniques. The results of this study indicate that most tourist visits, umkm, restaurants, and hotels have a significant effect on PAD. Tourist visits, umkm, official restaurants are not significant on PAD. Whereas the hotel is significant to PAD in Surabaya City.